Influence of the environment on the morphology, optical and electrical characteristics of the PEDOT:PSS polymer - К.С. Рожкова; А.К. Аймуханов; А.К. Зейниденов; А.М. Алексеев (Қарағанды университетінің хабаршысы. Физика сериясы)
The paper presents the results of studying the influence of the environment on the surface structure, optical and electrical characteristics of the PEDOT:PSS film. The studies have been carried out in three different types of atmosphere under the same conditions of thermal annealing of the films. It has been established that the modification of the surface of a polymer film with ethanol and isopropanol in vacuum, in a nitrogen atmosphere, and in the air atmosphere leads to a change in the surface morphology and the optical electric transport properties of the polymer. Depending on the environment, when the PEDOT:PSS film is modified with a certain concentration of ethyl and isopropyl alcohols, the absorption spectra show a shift in the absorption maximum responsible for PEDOT to the short-wavelength region of the spectrum, as well as a decrease in the absorption peak of the part of the spectrum responsible for the absorption of the aromatic fragment PSS. It is identified that the structural features of the PEDOT:PSS surface morphology affect the electrical transport parameters of the films: Rh is the resistance of the PEDOT:PSS polymer film, Rext is the charge carrier transfer resistance at the PEDOT:PSS/electrode interface, keff is the effective charge carrier extraction rate and τeff is the effective transit time of charge carriers. The optimal technological parameters for film production have been determined, at which the electrical transport properties of PEDOT:PSS polymer film are increased.